2014
DOI: 10.1111/cdev.12226
|View full text |Cite
|
Sign up to set email alerts
|

Children's Attractiveness, Gender, and Race Biases: A Comparison of Their Strength and Generality

Abstract: Although research suggests that facial attractiveness biases significantly affect social development and interactions, these biases are understudied in the developmental literature and are overlooked when designing interventions relative to gender and race. The authors, therefore, compared how much bias 3-11-year-olds (N=102) displayed in the three domains. They also examined whether bias and flexibility (understanding that different social groups can possess similar attributes) were related across domains. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 90 publications
2
27
0
Order By: Relevance
“…Moreover, these data contribute to a growing body of research demonstrating that in the presence of competing information (e.g., gender, attractiveness, accent, coalitions), younger White children often do not privilege race (e.g., Rennels & Langlois, 2014; Rhodes, 2013). Critically, these data suggest that even when the competing feature is highly salient but understood to be non-stable, young White children do not conceptualize race as stable.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Moreover, these data contribute to a growing body of research demonstrating that in the presence of competing information (e.g., gender, attractiveness, accent, coalitions), younger White children often do not privilege race (e.g., Rennels & Langlois, 2014; Rhodes, 2013). Critically, these data suggest that even when the competing feature is highly salient but understood to be non-stable, young White children do not conceptualize race as stable.…”
Section: Discussionmentioning
confidence: 79%
“…They believe that gender (more than race) marks different “kinds” of people (Rhodes & Gelman, 2009), and when asked with whom they want to be friends or share preferences, they select children of the same-gender or same-accent, more than those of the same-race (Kinzler, Shutts, Dejesus, & Spelke, 2009; Shutts, Pemberton Roben, & Spelke, 2013). Children also privilege attractiveness, such that they infer that attractive people have positive traits and unattractive people have negative traits, and are less likely to make trait inferences on the basis of race (Rennels & Langlois, 2014). …”
mentioning
confidence: 99%
“…During the preschool years, children play more amicably when they are similar in attractiveness rather than dissimilar in attractiveness (Langlois & Downs, 1979). Moreover, the children in this study showed very strong displays of bias based on attractiveness (Rennels & Langlois, 2014). Adults rated the attractiveness of individuals in these studies, so these differential judgments and behaviors provide strong evidence that very young children perceive attractiveness similarly to adults and make functional use of attractiveness during social interactions; our results show they just do not yet have a well-established concept of this classification.…”
Section: Discussionmentioning
confidence: 70%
“…They were also less accurate at sorting and labeling others by attractiveness than by gender or race and showed no agreement with adults in how they self-rated their attractiveness compared to strong agreement with adults in how they self-rated their gender or skin tone. Children’s concept of attractiveness therefore appears to be less explicit and less developed than that of gender and race, even though their perception of attractiveness is at a relatively adult-like level as evidenced by these same children showing strong attractiveness biases (Rennels & Langlois, 2014). These results suggest children may be less aware of their functional use of attractiveness to judge others compared to gender and race, which may impact their ability to control such bias (Devine, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation